RELASI KEPEMIMPINAN DAN EFIKASI DIRI DOSEN SEBAGAI DAYA UNGKIT KINERJA TRI DHARMA PERGURUAN TINGGI - Kusumah, Danial (LPPM IAIT, 2025)
This research aims to examine the relationship between leadership and lecturer self-efficacy and its impact on the performance of the tri dharma of higher education. In order for the research to achieve its objectives, researchers used qualitative research methods with a documentation study approach. The results of the study conclude that there is a strong and reciprocal relationship between leadership and lecturer self-efficacy. Leaders who are able to build good communication channels, in formal and informal spaces, will create positive leverage for the performance of lecturers in fulfilling the tri dharma obligations of higher education. Keywords: Leadership, Lecturer Self-Efficacy, Performance